Heidegger, translation, and the task of thinking essays in honor of Parvis Emad - Schalow, F.; SpringerLink (Online service). (Dordrecht Springer Netherlands, 2011)
Numerous volumes have been written on the philosophy of Martin Heidegger, and new translations of his writings appear on a regular basis. Up to now, however, no book has addressed the connections between Heidegger's thought and the hermeneutic methodology involved in translating his works - or any other text. Gathering essays by internationally recognized scholars, this volume examines the specific synergy that holds between Heidegger's thinking and the distinctive endeavor of translation. Heidegger, Translation, and the Task of Thinking: Essays in Honor of Parvis Emad offers scholars and students alike a rare journey into the insights and intricacies of one of the greatest philosophers of the twentieth century. The book also pays homage to Parvis Emad, Professor Emeritus of Philosophy at De Paul University, founder of the journal Heidegger Studies and a renowned translator of Heidegger?s writings. Heidegger, Translation, and the Task of Thinking: Essays in Honor of Parvis Emad provides a uniquely focused perspective on Heidegger's thought, and delves into the strategies and controversies that attend all attempts to translate his most complex and challenging texts, including his seminal works Contributions to Philosophy and Mindfulness. Accordingly, this book will be of great interest and benefit to anyone working in the fields of phenomenology, hermeneutics, or Heidegger studies.
Acknowledgments.- Preface.- PART 1: HEIDEGGER?S PATHWAY.- Poverty; Martin Heidegger_ translated by Thomas Kalary and Frank Schalow.- Introduction; Frank Schalow.- PART II: THE SEARCH FOR BEGINNINGS AND THE ONSET OF BEING-HISTORICAL THINKING.- Deformalization and Phenomenon in Husserl and Heidegger; Burt C. Hopkin.- A Purview of Being: The Ontological Structure of World, Reference (Verweisung) and Indication (Indikation); Marylou Sena.- Heidegger?s Experience with Language; George Kovacs.- Heidegger?s Thinking of Difference and the God-question; Thomas Kalary.- Substance and Emptiness: Preparatory Steps toward a Translational Dialogue between Western and Buddhist Philosophy; Paola-Ludovika Coriando_translated by Virginia Lyle Jennings Colombo.- Preliminary Notes on Divine Images in the Light of Being-Historical Thinking; Bernhard Radloff.- PART III: THE PLACE OF TRANSLATION IN HEIDEGGER?S THINKING.- A Conversation with Parvis Emad on the Question of Translation in Heidegger; Frank Schalow.- Heidegger?s Contributions to Philosophy: The Challenge of its Translation; George Kovacs.- Dasein and Da-sein in Being and Time and in Contributions to Philosophy (From Enowning); Friedrich-Wilhelm von Herrmann_translated by Bernhard Radloff.- Husserl and Heidegger on Da-sein: With a Suggestion for Its Interlingual Translation; Ivo De Gennaro.- Heidegger, Hölderlin, and Eccentric Translation; Julia A. Ireland Individuation, Responsiveness, Translation: Heidegger?s Ethics; Eric Sean Nelson.- Attunement and Translation; Frank Schalow.- Appendix: Parvis Emad?s List of Publications.- Selected Bibliography.- Contributors.- Index.
Electronic reproduction.
Keywords: Heidegger, Martin -- 1889-1976.; Thought and thinking; Electronic books